Speech Activity Detection and its Evaluation in Speaker Diarization System - Kaur, Sukhvinder; Sohal, J. S. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
In speaker diarization, the speech/voice activity detection is performed to separate speech, non-speech and silent frames. Zero crossing rate and root mean square value of frames of audio clips has been used to select training data for silent, speech and nonspeech models. The trained models are used by two classifiers, Gaussian mixture model (GMM) and Artificial neural network (ANN), to classify the speech and non-speech frames of audio clip. The results of ANN and GMM classifier are compared by Receiver operating characteristics (ROC) curve and Detection ErrorTradeoff (DET) graph. It is concluded that neural network based SAD comparatively better than Gaussian mixture model based SAD.